An adaptively controlled modified atmosphere container system for fresh produce. (August 2016) - Lee, Ji Hye; An, Duck Soon; Song, Jae Min; Jung, Yong Bae; Lee, Dong Sun
Abstract : Time-variable open/close cycles of a gas diffusion tube may serve as a means to supply the desired gas transfer to attain a beneficial modified atmosphere (MA) in fresh produce containers. Because the produce respiration contributing to the atmosphere modification changes over time, adoption of real-time respiration in the open/close control of the tube may be an innovative tool to maintain the container atmosphere. An adaptive control of the tube responding to the real-time respiration of fresh produce was developed based on a simplified O2 mass balance to generate and maintain the desired MA for the fresh produce. Here, the O2 concentration change in the initially closed container before reaching the target value was used to calculate the respiration rate to determine the starting value of the opening ratio of the cycle time and the average O2 concentration of each cycle after reaching the target value once was used in the mass balance relationship to update the opening ratio for the next cycle. The developed MA container system could attain the targeted O2 concentrations and the expected desirable CO2 concentrations for blueberries and spinach at steady state, helping to preserve their quality. Graphical abstract: Highlights: Adaptive control logic to keep the desired MA in fresh produce container. [O2 ] along with respiration was used to control opening time ratio of diffusion tube. The system could attain the target MAs for blueberries and spinach at steady state. The MA container system helped to preserve produce quality.